2017
DOI: 10.1515/sgem-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Code Calculations for Local Stability of Shaft Guides

Abstract: Steel structures for a conveyance guiding system are subjected to prolonged, intense corrosion during their operation leading to a considerable loss of material and structure capacity reduction. Shaft guides are made of closed profiles welded from hotrolled channel sections. These profiles are categorized as class 1 cross-sections according to Eurocode 3, which means that they are resistant to local instability upon bending [1]. With an increase in the corrosion loss of the guides, the inertia moment of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The determined experimental load-carrying capacity was significantly lower than the bending moment resistance calculated on the basis of standard calculations due to the significant influence of shear force in the three-point bending test. The effect of uniform corrosion on channel sections welded to form a box-section beam was investigated by Fiołek et al [ 18 ] and Fiołek and Jakubowski [ 19 ]. By performing laboratory and numerical bending tests, they showed the effect of uniform corrosion on the local buckling resistance of analyzed box beam profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determined experimental load-carrying capacity was significantly lower than the bending moment resistance calculated on the basis of standard calculations due to the significant influence of shear force in the three-point bending test. The effect of uniform corrosion on channel sections welded to form a box-section beam was investigated by Fiołek et al [ 18 ] and Fiołek and Jakubowski [ 19 ]. By performing laboratory and numerical bending tests, they showed the effect of uniform corrosion on the local buckling resistance of analyzed box beam profiles.…”
Section: Introductionmentioning
confidence: 99%
“…These profiles are used as guides in the construction of shaft steelwork [ 20 ] and are exposed to atmosphere [ 21 , 22 ], erosion [ 23 ], and mine water [ 24 ] corrosion. Furthermore, high humidity and temperature resulted in high corrosion loss, which is unusual for civil engineering structures [ 18 , 19 , 25 ]. The tested beams were exposed to an underground corrosion environment for over 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…the cl allowed by the regulations in Poland [18] is 50% of the nominal wall thickness of the cross-section. Fiołek et al [44] presented studies on the load-carrying capacity of shaft guides as a function of uniform cl with reference to the eurocode 3 (ec3) standards [45]. a series of Fem numerical tests were performed for the selected profile, which exhibited high compliance with the standard calculations.…”
Section: Load-carrying Capacitymentioning
confidence: 99%
“…11) [49]. the resistance assessment considered the sensitivity to local buckling [44,46,47] and the uncertainty of the steel strength properties [52]. The load effects and resistance probability distributions enabled a probabilistic shaft steelwork reliability analysis.…”
Section: Structural Reliabilitymentioning
confidence: 99%
“…They accounted for the impact of structural weakness resulting from corrosion in steelwork elements. Experimental research on the load-carrying capacity of shaft guides was conducted by Fiołek and Jakubowski [9] and Fiołek et al [10]. They showed that high corrosion loss reduces the resistance to local buckling of hotrolled profiles.…”
Section: Introductionmentioning
confidence: 99%